2010
DOI: 10.1148/radiol.09090570
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Birth Injury: US Screening for Glenohumeral Joint Instability

Abstract: US is a fast and useful tool for diagnosis of posterior subluxation of the humeral head, and examination of the glenohumeral joint should be performed at 3 and 6 months of age in infants with BPBI if symptoms persist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 22 publications
3
51
0
Order By: Relevance
“…The important question of when to best identify infantile shoulder dislocations was addressed by Pöyhiä and colleagues 15 , who found posterior glenohumeral joint subluxation (defined as an alpha angle of >30°) in one-third of infants with permanent BPBP. In their study, 24 infants had shoulder ultrasound performed at 1, 3, 6, and 12 months of age; 5 of the 9 cases of glenohumeral joint subluxation were identified at 3 months of age and 8 of the 9, by 6 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…The important question of when to best identify infantile shoulder dislocations was addressed by Pöyhiä and colleagues 15 , who found posterior glenohumeral joint subluxation (defined as an alpha angle of >30°) in one-third of infants with permanent BPBP. In their study, 24 infants had shoulder ultrasound performed at 1, 3, 6, and 12 months of age; 5 of the 9 cases of glenohumeral joint subluxation were identified at 3 months of age and 8 of the 9, by 6 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Obstetrical Brachial Plexus Palsy (OBPP) is a common birth injury, occurring in approximately three in every 1000 births 3; 26; 29; 37 . Children who do not recover completely are left with shoulder muscle imbalance, contracture, disuse, and significant glenoid-humeral deformities 20; 24; 40; 41; 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) glenoid retroversion and glenohumeral subluxation have been well studied in OBPP 10; 21; 23; 27; 34; 37 , but few studies have quantified humeral deformity in isolation. The studies that have focused on humeral pathology demonstrated atrophy 28; 37; 38 and “retroversion” on the involved side 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound has previously been reported as a useful tool in screening for instability in this joint. 13 Longstanding muscle imbalances in the shoulder girdle can result in progressive glenohumeral joint deformity and joint dysplasia. Patients can also develop functionally limiting internal rotation contractures that require subsequent surgical intervention.…”
Section: Discussionmentioning
confidence: 99%